Penerapan Kriteria Penilaian Prestasi Kerja Dalam Peningkatan Profesionalisme Tenaga Kependidikan - Ahmad Hadiq Syifa Al Fawaz (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to analyze the effectiveness of the implementation of performance assessment criteria in improving the professionalism of education personnel at MAN 2 Banyuwangi. The results showed that the implementation of clear and structured assessment criteria contributed to a significant increase in the performance and professionalism of education personnel. The education personnel involved showed higher activity in self-development, training, and participation in school activities. The evaluation also noted improvements in task management and work methods, indicating that the implementation of appropriate assessment criteria can improve the quality of teaching and the professional atmosphere in the educational environment. This study used a qualitative approach with thematic analysis type to explore the implementation of performance assessment criteria at MAN 2 Banyuwangi. This location was chosen because of the relevance of the assessment policy applied to the focus of the study. Data were collected through in-depth interviews, observations, and document studies, with informants selected using purposive sampling to ensure the relevance of the information. Data analysis techniques involved coding and grouping themes, while the validity of the data was checked through triangulation, member checking, and audit trails. The results showed that the implementation of assessment criteria served to improve the quality of teaching by setting measurable standards in various aspects of teaching. Curriculum adjustments, ongoing training, and self-development programs contribute to improving the professionalism of education personnel. Satisfaction and motivation of education personnel are also considered as important factors in teaching effectiveness. Overall, the implementation of structured assessment criteria not only improves the quality of teaching but also supports teacher career development and job satisfaction.